2021
DOI: 10.21203/rs.3.rs-58757/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ITGA5 is a prognostic biomarker and correlated with immune infiltration in gastrointestinal tumors

Abstract: Background: Integrin Subunit Alpha 5 (ITGA5), belongs to the integrin alpha chain family, is vital for promoting cancer cell invasion, metastasis. However, the correlation between ITGA5 expression and immune infiltration in gastrointestinal tumors remain unclear.Methods: The expression level of ITGA5 was detected by Oncomine and Tumor Immune Estimation Resource (TIMER). The association between ITGA5 and prognosis of patients was identified by Kaplan–Meier plotter, Gene Expression Profiling Interactive Analysis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…LAMB combines with LAMC; together, they initiate cell assembly to promote cancer invasion and gene expression in various invasive cancers, including LAMB1 gene expression in head and neck, liver, and uterine endometrial cancers, and LAMC1 gene expression in gastric cancer [28][29][30]. Integrin subunits α5 and β1 primarily conjoin to form α5β1 heterodimers, and ITGA5 and ITGB1, the genes encoding α5 and β1, respectively have been suggested to be associated with tumor aggressive behavior, such as cancer progression and treatment resistance [31,32]. In our study, an increase in ITGA5 and ITGB1 expression was characteristically identified in highrisk HPV (+) and HPV (-) groups in HNC, and was associated with the worsening OS in both HPV-related HNC and CC.…”
Section: Discussionmentioning
confidence: 99%
“…LAMB combines with LAMC; together, they initiate cell assembly to promote cancer invasion and gene expression in various invasive cancers, including LAMB1 gene expression in head and neck, liver, and uterine endometrial cancers, and LAMC1 gene expression in gastric cancer [28][29][30]. Integrin subunits α5 and β1 primarily conjoin to form α5β1 heterodimers, and ITGA5 and ITGB1, the genes encoding α5 and β1, respectively have been suggested to be associated with tumor aggressive behavior, such as cancer progression and treatment resistance [31,32]. In our study, an increase in ITGA5 and ITGB1 expression was characteristically identified in highrisk HPV (+) and HPV (-) groups in HNC, and was associated with the worsening OS in both HPV-related HNC and CC.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, ITGA4 has also been found highly expressed in chronic lymphocytic leukemia [45], and colorectal tumors [46]. Upregulation of ITGA5 was detected in gastric cancer [47]. ITGA7 was markedly up-regulated in breast cancer [48], prostate cancer [49], and non-small-cell lung cancer [50].…”
Section: Discussionmentioning
confidence: 99%
“…Integrin α5 (ITGA5) primarily binds to integrin β1 to form α5β1-integrin [9], which is highly expressed on the developing axons, the regenerating neurites and Schwann cells within the injured nerves, and performs vital functions in neural development and regeneration [24]. Meanwhile, ITGA5 overexpressed in multiple types of cancer and is essential for aggressive behaviors of tumors, including HNSCC [53]. Muscle glycogen phosphorylase or myophosphorylase (PYGM) is considered as a key enzyme in glycogen degradation existing in the muscular system and astrocytes in the central nervous system [14,33].…”
Section: Neural-related Signature Genes Of Nrgrsmentioning
confidence: 99%